Examining the Effects of Exercise on Neuroplasticity and Depression Disorder: Implications for Depression Treatment - Amaranggani, Anindhita P; Ritmiani, Iklima; Indry Dubu, Rema Vara; Hariati, Rima; Nasution, Zararah Yusri (Universitas Pekalongan, 2023)
Depression is a serious public health issue with a high risk of mortality and limited access to pharmacological and psychotherapeutic treatments. Exercise serves as an effective and readily accessible alternative intervention in addressing depression by influencing brain neuroplasticity and various aspects of mental health. This article is an integrative review that analyzes the potential of brain neuroplasticity in reducing depression symptoms through exercise, exploring literature related to depression, exercise, and neuroplasticity to generate implications for depression management. The article was retrieved via Google Scholar, and a synthesis of 38 relevant articles was conducted. The results indicate that depression affects brain structure and function, which are also associated with neuroplasticity. Exercise has the potential to stimulate brain neuroplasticity, particularly in areas affected by depression, such as the hippocampus and prefrontal cortex. This potential makes exercise an effective yet cost-effective and easily accessible alternative for the prevention and treatment of depression, especially mild to moderate depression.